Pulegone Prevents Hypertension through Activation of Muscarinic Receptors and Cyclooxygenase Pathway in L-NAME-Induced Hypertensive Rats - Muryam Abdul Razzaq; Waqas Younis; Muhammad Nasir Hayat Malik; Tariq G. Alsahli; null Alamgeer; Shah Jahan; Roma Ehsan; Arquimedes Gasparotto Junior; Asifa Bashir (Cardiovascular Therapeutics)
The current study was designed to determine pulegone’s antihypertensive and vasoprotective activity in L-NAME-induced hypertensive rats. Firstly, the hypotensive dose-response relationship of pulegone was evaluated in normotensive anesthetized rats using the invasive method. Secondly, the mechanism involved in hypotensive activity was determined in the presence of pharmacological drugs such as atropine/muscarinic receptor blocker (1 mg/kg), L-NAME/NOS inhibitor (20 mg/kg), and indomethacin/COX inhibitor (5 mg/kg) in anesthetized rats. Furthermore, studies were carried out to assess the preventive effect of pulegone in L-NAME-induced hypertensive rats. Hypertension was induced in rats by administering L-NAME (40 mg/kg) orally for 28 days. Rats were divided into six groups which were treated orally with tween 80 (placebo), captopril (10 mg/kg), and different doses of pulegone (20 mg/kg, 40 mg/kg, and 80 mg/kg). Blood pressure, urine volume, sodium, and body weight were monitored weekly. After 28 days, the effect of pulegone on lipid profile, hepatic markers, antioxidant enzymes, and nitric oxide was estimated from the serum of treated rats. Moreover, plasma mRNA expression of eNOS, ACE, ICAM1, and EDN1 was measured using real-time PCR. Results show that pulegone dose-dependently decreased blood pressure and heart rate in normotensive rats, with the highest effect at 30 mg/kg/i.v. The hypotensive effect of pulegone was reduced in the presence of atropine and indomethacin, whereas L-NAME did not change its hypotensive effect. Concurrent treatment with pulegone for four weeks in L-NAME-treated rats caused a reduction in both systolic blood pressure and heart rate, reversed the reduced levels of serum nitric oxide (NO), and ameliorated lipid profile and oxidative stress markers. Treatment with pulegone also improved the vascular response to acetylcholine. Plasma mRNA expression of eNOS was reduced, whereas ACE, ICAM1, and EDN1 levels were high in the L-NAME group, which was facilitated by pulegone treatment. To conclude, pulegone prevented L-NAME-induced hypertension by demonstrating a hypotensive effect through muscarinic receptors and cyclooxygenase pathway, indicating its use as a potential candidate in managing hypertension.